Non-invasive oocyte quality assessment. Issue 2 (5th February 2022) - Sciorio, Romualdo; Miranian, Daniel; Smith, Gary D
Abstract: Oocyte quality is perhaps the most important limiting factor in female fertility; however, the current methods of determining oocyte competence are only marginally capable of predicting a successful pregnancy. We aim to review the predictive value of non-invasive techniques for the assessment of human oocytes and their related cells and biofluids that pertain to their developmental competence. Investigation of the proteome, transcriptome, and hormonal makeup of follicular fluid, as well as cumulus-oocyte complexes are currently underway; however, prospective randomized non-selection-controlled trials of the future are needed before determining their prognostic value. The biological significance of polar body morphology and genetics are still unknown and the subject of debate. The predictive utility of zygotic viscoelasticity for embryo development has been demonstrated, but similar studies performed on oocytes have yet to be conducted. Metabolic profiling of culture media using human oocytes are also limited and may require integration of automated, high-throughput targeted metabolomic assessments in real time with microfluidic platforms. Light exposure to oocytes can be detrimental to subsequent development and utilization of time-lapse imaging and morphometrics of oocytes is wanting. Polarized light, Raman microspectroscopy, and coherent anti-Stokes Raman scattering are a few novel imaging tools that may play a more important role in future oocyte assessment. Ultimately, the integration of chemistry, genomics, microfluidics, microscopy, physics, and other biomedical engineering technologies into the basic studies of oocyte biology, and in testing and perfecting practical solutions of oocyte evaluation, are the future for non-invasive assessment of oocytes. Abstract : Direct and/or indirect non-invasive assessments of oocyte quality are reviewed and discussed in relation to clinical needs in assisted reproductive technologies and as informative underpinnings of basic reproductive biology spanning follicle to embryo development.